The given differential equation can be written as "(D^{3}-D)y = 5t,~ \\text{where}~ D\\equiv \\dfrac{d}{dt}."
The auxiliary equation is, "m^{3}-m=0." Solving, we get "m = 0,1,-1."
The complementary function is, "y_{c} = c_{1}+c_{2}e^{t}+c_{3}e^{-t} = c_{1}f_{1}+c_{2}f_{2}+c_{3}f_{3}"
The particular integral is "y_{p}=Pf_{1}+Qf_{2}+Rf_{3}," where
"P=\\displaystyle\\int \\frac{W_{1}}{W(f_{1},f_{2},f_{3})}dx; Q=\\displaystyle\\int \\frac{W_{2}}{W(f_{1},f_{2},f_{3})}dx;\\\\~\\\\ R=\\displaystyle\\int \\frac{W_{3}}{W(f_{1},f_{2},f_{3})}dx;"
and "W_{i}" is the determinant obtained from the Wronskian "W(f_{1},f_{2},f_{3})" by replacing the "i^{th}" - column by the vector "\\begin{pmatrix} 0 \\\\ 0 \\\\ g(t) \\end{pmatrix}" where "g(t) = 5t."
Now,
"W(f_{1},f_{2},f_{3}) = \\begin{vmatrix} 1 & e^{t} & e^{- t} \\\\ 0 & e^{t} &- e^{- t} \\\\0 & e^{t} & e^{- t} \\end{vmatrix} = 2\\\\~\\\\\nW_{1} = \\begin{vmatrix} 0 & e^{t} & e^{- t} \\\\ 0 & e^{t} &- e^{- t} \\\\5t & e^{t} & e^{- t} \\end{vmatrix} = -10t\\\\~\\\\\nW_{2} = \\begin{vmatrix} 1 & 0 & e^{- t} \\\\ 0 & 0 &- e^{- t} \\\\0 & 5t & e^{- t} \\end{vmatrix} = 5te^{-t}\\\\~\\\\\nW_{3} = \\begin{vmatrix} 1 & e^{t} & 0 \\\\ 0 & e^{t} & 0 \\\\0 & e^{t} &5t \\end{vmatrix} = 5te^{t}"
Therefore,
"P = \\displaystyle\\int -5t~ dt = -\\frac{5t^{2}}{2}\\\\~\\\\\nQ= \\displaystyle \\frac{5}{2}\\int te^{-t}~ dt = \\frac{5}{2}(-te^{-t}-e^{-t}) = -\\frac{5}{2}e^{-t}(t+1)\\\\~\\\\\nR= \\displaystyle \\frac{5}{2}\\int te^{t}~ dt = \\frac{5}{2}(te^{t}-e^{t}) = \\frac{5}{2}e^{t}(t-1)"
Hence,
"\\begin{aligned}\ny_{p} &=Pf_{1}+Qf_{2}+Rf_{3}\\\\\n&=-\\frac{5t^{2}}{2}-\\frac{5}{2}e^{-t}(t+1) \\cdot e^{t} + \\frac{5}{2}e^{t}(t-1) \\cdot e^{-t}\\\\\n&=-\\frac{5t^{2}}{2}-\\frac{5}{2}(t+1) + \\frac{5}{2}(t-1)\\\\\n&=-\\frac{5t^{2}}{2} - 5\n\\end{aligned}"
The general solution is
"\\begin{aligned}\ny = y_{c}+y_{p} &= c_{1}+c_{2}e^{t}+c_{3}e^{-t}-\\dfrac{5t^{2}}{2}-5\\\\\ny&= C_{1}+c_{2}e^{t}+c_{3}e^{-t}-\\dfrac{5t^{2}}{2}, \\text{where}~C_{1}=c_{1}-5.\n\\end{aligned}"
Comments
Leave a comment